2000
DOI: 10.1007/bf02237357
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of omentoplasty in preventing leakage of colorectal anastomosis

Abstract: Despite a similar incidence of staple-ring defects, a strikingly lower rate of clinically and radiologically detected leaks developed in patients submitted to omentoplasty. Although not affecting the incidence of anastomotic disruption, omentoplasty seems to contain the severity of anastomotic leakage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 18 publications
3
46
0
2
Order By: Relevance
“…Unfortunately, many of these attempts have failed to show convincing results [18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48]. Numerous studies have reported on the sealing of gastrointestinal anastomoses with fibrin glue (FG), also called fibrin sealant.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, many of these attempts have failed to show convincing results [18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48]. Numerous studies have reported on the sealing of gastrointestinal anastomoses with fibrin glue (FG), also called fibrin sealant.…”
Section: Introductionmentioning
confidence: 99%
“…In order to prevent leakage postoperatively and to decrease recurrent ureteral obstruction with a progression of residual pelvic malignancy we used a tissue transplant of greater omentum or rectus abdominus muscle [10]. In none of our patients was recurrent ureteral obstruction apparent on follow-up computed tomography.…”
Section: Discussionmentioning
confidence: 91%
“…This was an omental pedicle flap in four and a rectus abdominus muscle flap in one patient [10]. These transplants of highly vascularized tissue to the anastomotic site of the ureters was utilized when possible; they may be of special importance in patients who have had prior radiotherapy.…”
Section: Figmentioning
confidence: 99%
“…Omentum, peritoneal patches and dura mater have been tested as biological materials [7][8][9][10][15][16][17] . Polyglycolic acid mesh, Dacron, Marlex and artificial collagen or elastin membranes have been evaluated experimentally as synthetic materials [6,7,12,14] .…”
Section: Discussionmentioning
confidence: 99%
“…Covering of gastrointestinal anastomoses by materiminatory systemic consequences of anastomotic dehiscence appears to be a promising approach for the prevention of anastomotic leakage. In the literature, various biological and artificial materials have been studied for anastomotic reinforcement [6][7][8][9][10][11][12][13][14][15][16][17] . Bio-Gide (BG) is a novel biodegradable non-cross-linked collagenous matrix extracted from porcine dermis, which is ultrastructurally characterized by two different surface structures on both sides of the membrane.…”
Section: Introductionmentioning
confidence: 99%